Efektivitas Pengomposan Sampah Organik Menggunakan Mikroorganisme Lokal Sabut Kelapa dan Nasi Bekas - Syarmilahtus Surotin; Yayok Suryo Purnomo (Jurnal Serambi Engineering, 2024)
Currently, the most waste comes from households at 38.4%. Efforts to deal with these problems are made by making compost with the addition of bioactivators to speed up the composting process. The purpose of this study was to compare the results of compost with the addition of variations of coconut husk MOL, used rice MOL, combinations MOL and get the best results in accordance with SNI 19-7030-2004. This study used raw materials from household organic waste and MOL variations, namely coconut husk, used rice, and a mixture of both. In addition, it also uses variations in the dose of MOL, namely 5ml and 10ml. This study showed that the addition of MOL variations was more effective than control variations. The results showed that MOL coconut husk and used rice have a high bacterial content so that they can be used as bioactivators, compost results based on physical parameters have met SNI, namely having a blackish color, earth-like texture, and smelling of soil. Compost with the addition of a bioactivator (MOL) mixture of coconut husk and used rice dose of 10ml has a C/N ratio value of 15.14 and a high reduction rate of 63.80%. This variation is more effective in degrading organic waste compared to other variations. The use of natural bioactivator materials is environmentally friendly, economical and also more effective in degrading household organic waste.